2018
DOI: 10.1016/j.ejvs.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Cerebral Hyperperfusion Syndrome After Carotid Artery Stenting: A Systematic Review and Meta-analysis

Abstract: CHS is a serious and frequent complication in patients undergoing carotid angioplasty with stenting, and is most likely to occur in the very early post-procedural period. Future studies are encouraged to investigate the effect of intensive haemodynamic monitoring, including blood pressure control and assessment of cerebral blood flow, on the incidence of stroke caused by CHS after CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 25 publications
0
46
1
3
Order By: Relevance
“…Стенозирующее поражение сонных артерий как правило представляет из себя конгломерат жесткой кальцифицированной атеромы в зоне бифуркации общей сонной артерии и в устье внутренней сонной артерии [4]. Помимо первичной и вторичной профилактики развития ОНМК, эндоваскулярная реваскуляризация и имплантация стента в зону каротидного синуса имеет влияния на уровень артериального давления (АД) [5]. В этой зоне расположены барорецепторы каротидного сплетения, их реакцией на растяжение артериальной стенки является обеспечение обратной связи с центром регуляции АД.…”
Section: The Dynamics Of Blood Pressure Within 12 Months After Carotiunclassified
See 1 more Smart Citation
“…Стенозирующее поражение сонных артерий как правило представляет из себя конгломерат жесткой кальцифицированной атеромы в зоне бифуркации общей сонной артерии и в устье внутренней сонной артерии [4]. Помимо первичной и вторичной профилактики развития ОНМК, эндоваскулярная реваскуляризация и имплантация стента в зону каротидного синуса имеет влияния на уровень артериального давления (АД) [5]. В этой зоне расположены барорецепторы каротидного сплетения, их реакцией на растяжение артериальной стенки является обеспечение обратной связи с центром регуляции АД.…”
Section: The Dynamics Of Blood Pressure Within 12 Months After Carotiunclassified
“…В этой зоне расположены барорецепторы каротидного сплетения, их реакцией на растяжение артериальной стенки является обеспечение обратной связи с центром регуляции АД. Как следствие частым проявлением КАС является нестабильность АД в раннем послеоперационном периоде [5][6][7]. Однако долгосрочное влияние КАС на изменение АД, а также предикторы развития гипотензивного эффекта, недостаточно изучены.…”
Section: The Dynamics Of Blood Pressure Within 12 Months After Carotiunclassified
“…We read with great interest the systematic review and meta-analysis by Wang et al, on the impact of frailty on the outcome of elderly patients after major vascular surgery. 1 The authors present a nice detailed overview of current frailty papers. In their extensive analysis they evaluate multiple frailty tools, both single and multi-domain assessment tools, in major vascular surgery.…”
Section: The Many Faces Of Frailty In Vascular Surgerymentioning
confidence: 99%
“…We have read the meta-analysis by Huibers et al 1 regarding cerebral hyperperfusion syndrome (CHS) after carotid artery stenting, but some points should be addressed. Firstly, the authors found that CHS is a frequent complication after carotid artery stenting (CAS) leading to a high stroke rate.…”
mentioning
confidence: 99%
“…Paradox Findings are Reality, Difficult is the Explanation In their article "Lower limb deep vein diameters beneath medical compression stockings in the standing position", Rastel et al concluded that in the standing position, deep vein diameter reduction is not caused by medical compression stockings (MCSs) but may be due to the isometric muscle contractions. 1 There is some doubt if this simple message is the full truth, as we would expect to see the effect regularly, even without any compression, which is not the case. Quite the opposite: the diameter of deep veins is usually larger without compression in the standing vs. recumbent position.…”
mentioning
confidence: 97%